THE EFFECT OF REPLACING COMMERCIAL RATION WITH CRICKET FLOUR (Gryllus mitratus burm) ON INCOME OF BROILER FARMERS - I. N., Caroline; Sukanata, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This research aimed to determine the income of broiler farms that use cricket flour ( Gryllus mitratus Burm ) as a substitute for commercial rations. This research was carried out for 24 days at the Teaching Farm, Faculty of Animal Husbandry, Udayana University, Jl. Passion Fruit No.6, Sesetan, Denpasar, Bali. The design used in this research was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, and in each replication 4 broilers were used so that a total of 64 broilers were used. The treatments given were: P0: commercial ration without replacement with cricket flour; P1: 2% of commercial diet replaced with cricket flour; P2: 4% of commercial diet replaced with cricket flour; and P3: 6% of commercial ration replaced with cricket flour. Observed variables include costs, revenues, income, R/C ratio and break-even point (BEP). The results of this research show that giving cricket flour to broilers can increase breeder income. The P3 treatment gave the best results with an income of IDR 11,294/head (88.74% higher than P0) with an R/C ratio of 1.213 (7.44% higher than P0), and a break-even price of IDR 22,961 /kg live weight (7.10% lower than P0). The income obtained from treatments P1 and P2 was IDR 5,989/head and IDR 7,371/head respectively. Meanwhile, the R/C values of these treatments were 1.121 and 1.146 respectively.